Hydro-conditioning and seed partitioning for Inga laurina (SW.) Willd Propagation - Porto, Alexandre Hack; Júnior, Américo Wagner; Neto, Carlos Kosera; Voss, Larissa Corradi; Moura, Gisely Corrêa de; Radaeli, Juliana Cristina (Scientia Agraria Paranaensis, 2021)
The Inga laurina (Sw.) Willd species comes from tropical and subtropical regions, in several phytogeographic areas of distribution, including Brazil. It belongs to the leguminous family, present in riparian forests and used in urban afforestation, it provides shading and a pleasant microclimate, ornamental value, in addition to the fruit being consumed by man and birds. Species of this genus have compounds that are used in popular medicine. The propagation method is still by seeds, making it difficult to obtain the seedling, as they present recalcitrance, impairing its storage viability. The objective of this work was to verify the possibility of I. laurina seeds partitioning for the species propagation, and the storage viability, if previously subjected to hydro-conditioning. A completely randomized design was adopted, in a 2 x 4 factorial (Lot x storage time), with four replications of 50 seeds per experimental unit. The treatments were formed by the lots of whole and partitioned seeds, plus the hydro-conditioning application in the stored period. After the treatment’s application, sowing was done in tubes, being kept in a 120-day evaluation period. After this period, emergence, emergence speed index, average emergence time, air length and roots (cm), the aerial part and roots dry biomass (g), number of roots, leaves and stems (g) were evaluated. Seed partitioning was not proved to be advantageous. The seed partitioning technique was not proved to be advantageous. The hydro-conditioning adoption during storage allowed the seeds to remain viable and with the desired vigor.